An Empirical Study to Find the Gaps in Call Coverage and its Impact on Sales Performance - Gupta, Sunil (Indian Journal of Marketing, 2011)
In the current market situation, the companies are facing more and more difficulties in implementing the strategies at the market place and failing to do so, results in poor sales performance. McKinsey published report on Sales force effectiveness and has shown that due to pressures of time and more complex market situation, sales people effectiveness is going down over a period and which largely effects the ROI of the companies. Therefore, the most important aspect is coverage of customers by sales representatives & this paper has briefly discussed issues like call adherence level, call frequencies and the gaps which have direct bearing on sales performance of companies and have suggested measures to overcome so as to excel in sales performance.